2016
DOI: 10.1002/ajh.24285
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric‐inspired therapy compared to allografting for Philadelphia chromosome‐negative adult ALL in first complete remission

Abstract: For adults with Philadelphia chromosome negative (Ph-) acute lymphoblastic leukemia (ALL) in first complete remission (CR1), allogeneic hematopoietic cell transplantation (HCT) is an established curative strategy. However, pediatric-inspired chemotherapy may also offer durable leukemia free survival in the absence of HCT. We compared 422 HCT recipients aged 18-50 years with Ph-ALL in CR1 reported to the CIBMTR with an age-matched concurrent cohort of 108 Ph- ALL CR1 patients who received a Dana-Farber Consorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 39 publications
1
38
1
Order By: Relevance
“…A recent analysis of patients up to age 50 compared a pediatric inspired non-transplant approach to that of allogeneic HCT, using data from Dana Farber ALL consortium and the Center for International Blood and Marrow Transplant (CIBMTR), and reported comparable survival and relapse rates. 38 In our study of older adults, despite a low TRM of 13%, no survival benefit was detected for HCT in older adults (65% versus 53% at 2 years, p-value 0.43; 42% versus 38% at 3 years). A previous study of intensified regimens in older patients did not assess the role of HCT, although two of their 51 studied patients, one Ph+ and one Ph-, did undergo HCT.…”
Section: Discussioncontrasting
confidence: 61%
“…A recent analysis of patients up to age 50 compared a pediatric inspired non-transplant approach to that of allogeneic HCT, using data from Dana Farber ALL consortium and the Center for International Blood and Marrow Transplant (CIBMTR), and reported comparable survival and relapse rates. 38 In our study of older adults, despite a low TRM of 13%, no survival benefit was detected for HCT in older adults (65% versus 53% at 2 years, p-value 0.43; 42% versus 38% at 3 years). A previous study of intensified regimens in older patients did not assess the role of HCT, although two of their 51 studied patients, one Ph+ and one Ph-, did undergo HCT.…”
Section: Discussioncontrasting
confidence: 61%
“…These findings were later confirmed in an individual-patient-data meta-analysis that pooled results from 13 studies [22]. A recent report suggested that patients 18-50 years of age had better outcomes with a pediatric-inspired, non-HSCT approach (Dana-Farber Consortium pediatric-inspired protocol) as compared to patients that received chemotherapy followed by HSCT in first remission [24]. Most of the studies that prospectively assessed postremission chemotherapy vs. HSCT were conducted in younger patients as compared to our cohort and used only matched related donors and a myeloablative preparative regimen.…”
Section: Discussionmentioning
confidence: 76%
“…In a recent retrospective analysis comparing 422 patients (18-50 years) having Ph-negative ALL who underwent alloHCT in first complete remission (CR) (as reported to the Center for International Blood and Marrow Transplantation Research [CIBMTR]) with 108 age-matched patients treated with the DFCI pediatric-inspired regimen, overall survival (OS) was better among patients who were treated with chemotherapy [51].…”
Section: Adopting Pediatric Regimens In Adultsmentioning
confidence: 99%